Temporal analysis of the evolution of the area irrigated by the central pivot, in the municipality of Unaí - MG (Research, Society and Development, 2022)
Knowledge of the availability and demand of water resources for irrigation is a first step towards giving water security to the region, being essential for decision-making aimed at efficient and sustainable water planning. In this context, geotechnologies, among them, geoprocessing, have provided broader, more accurate, and faster information, and can help in decision making, mainly due to the ability and ease of working in large areas.  The present work aims to evaluate the expansion of the irrigated area via the central pivot system in the municipality of Unaí (MG) and its relationship with the sub-basins that contribute to water resources in the municipality, through geoprocessing techniques.  The ANA ottocoded hydrological database was used, as well as metadata related to surveys of pivots at the Brazil level, made available on the portal of the National Information System on Water Resources (SNIRH).  As a result, it was found that the number of irrigated areas via the central pivot in Unaí, was increasing and constant over the years. In 2010, Unaí had 43,589 hectares with pivot, there was a growth of 52.9% compared to 2019. The methods used were able to provide valuable information, contributing to the knowledge of water use in the study region, and being fundamental for the planning and management of water resources.